Methylene Blue Reduces Neuronal Apoptosis and Improves Blood-Brain Barrier Integrity After Traumatic Brain Injury - Shen, Jun; Xin, Wenqiang; Li, Qifeng; Gao, Yalong; Yuan, Lili; Zhang, Jianning (Frontiers in Neurology, 2019)
Objective: To investigate whether Methylene blue (MB) treatment can reverse neuronal mitochondrial dysfunction caused by Oxygen Glucose Deprivation /reoxygenation (OGD) injury and then investigate whether MB treatment can reduce neuronal apoptosis and improve blood-brain barrier (BBB) integrity in TBI animals. Methods: Reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and adenosine triphosphate (ATP) were used to evaluate mitochondrial function. The Terminal deoxynucleotidyl transferase-dUTP nick end labeling (TUNEL) assay was used to assess neuronal apoptosis in vitro. TUNEL and immunofluorescence staining for neuronal nuclei (NeuN) were combined to assess neuronal apoptosis in vivo. An evans blue (EB) permeability assay and brain water content (BWC) were used to measure BBB permeability in vivo. The Morris water maze (MWM), rotarod test, and modified Neurological Severity Score (mNSS) test were employed to assess the prognosis of TBI mice. Results: MB treatment significantly reversed neuronal mitochondrial dysfunction caused by OGD injury. Both in vitro and in vivo, MB treatment reduced neuronal apoptosis and improved BBB integrity. In TBI animals, treatment with MB not only improved cognitive and motor function caused by TBI but also significantly improved overall neurological function. Conclusions: Our findings suggest that MB is a potential candidate for the treatment of TBI. Future research should focus on other therapeutic effects and mechanisms of MB in secondary brain injury.